Technology & School Reform: A View from Both Sides of the Tracks - Warschauer, Mark (Education Policy Analysis Archives, 2000)
A discourse of reform claims that schools must be transformed to take full advantage of computers, while a competing discourse of inequality warns that technology-enhanced reform is taking place only in wealthy schools, dooming poor and minority students to the wrong side of a digital divide. A qualitative study at an elite private school and an impoverished public school explored the relationship between technology, reform, and equality. The reforms introduced at the two schools appeared similar, but underlying differences in resources and expectations served to reinforce patterns by which the two schools channel students into different social futures.